1998
DOI: 10.1128/jb.180.4.932-937.1998
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Vibrio alginolyticus to Glass Surfaces Is Dependent on Swimming Speed

Abstract: The attachment of Vibrio alginolyticus to glass surfaces was investigated with special reference to the swimming speed due to the polar flagellum. This bacterium has two types of flagella, i.e., one polar flagellum and numerous lateral flagella. The mutant YM4, which possesses only the polar flagellum, showed much faster attachment than the mutant YM18, which does not possess flagella, indicating that the polar flagellum plays an important role. The attachment of YM4 was dependent on Na+ concentration and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The attractive force between the surface and the cell in the backward mode allows the cell to stay near the surface for a long time. Kogure et al (1998) reported the positive correlation between the probability of attachment to a glass surface and the swimming speed of V. alginolyticus. The results of our The cells were assumed to swim (e) near or ( f ) far from a surface in an environment in which the point source of an attractant was set at the distance of 1 mm from the origin (X ¼ 0 mm, Y ¼ 1000 mm).…”
Section: Significance Of the Surface For Bacteriamentioning
confidence: 99%
“…The attractive force between the surface and the cell in the backward mode allows the cell to stay near the surface for a long time. Kogure et al (1998) reported the positive correlation between the probability of attachment to a glass surface and the swimming speed of V. alginolyticus. The results of our The cells were assumed to swim (e) near or ( f ) far from a surface in an environment in which the point source of an attractant was set at the distance of 1 mm from the origin (X ¼ 0 mm, Y ¼ 1000 mm).…”
Section: Significance Of the Surface For Bacteriamentioning
confidence: 99%
“…This suggests that in some instances there was migration away from stimulant over time possibly as the resource was used up. The attachment of bacteria to the bead's surface may have been a function of bacteria colliding with the surface due to their high speed [21] while swimming through the band, as the band migrated closer to the bead when resources depleted.…”
Section: ) (196 þ 12 Cells Per Screen)mentioning
confidence: 99%
“…Vibrio alginolyticus 138-2 that had been maintained in the Microbiology Laboratory, Ocean Research Institute at the University of Tokyo, was precultured in 1/4-ZoBell 2216E culture medium at 27°C overnight. This medium contained polypeptone (1.25 g l -1 ) and yeast extract (0.25 g l -1 ) as organic substrates with artificial seawater, which was composed of the following compounds (l -1 of distilled water [pH 7.5]): NaCl, 23.4 g; KCl, 0.8 g; MgSO 4 •7H 2 O, 4 g; CaCl 2 , 0.2 g; KBr, 100 mg; SrCl 2 •6H 2 O, 26 mg; and H 3 BO 3 , 20 mg (Kogure et al 1998). The precultured cells were separated by centrifugation and washed twice with artificial seawater to remove the 1/4-ZoBell medium.…”
mentioning
confidence: 99%